Detection Algorithm of Alarm Messages Based on Linear Cooperative Strategy in VAENT - Xuefei Zhang; Guoan Zhang; Yancheng Ji (Dianxin kexue)
An alarm message detection algorithm for the traffic accident based on linear cooperative strategy in vehicular Ad Hoc network was proposed, and it was composed of two parts: local detection and global detection. Cluster heads received the statistics of detection signal strength from local mobile vehicle node, and conducted global linear combination to make a final decision. The numerical simulation results show that the proposed strategy can improve the detection probability within the scope of the false alarm probability, and avoid the broadcast storm.